Hubungan hygiene, sanitasi lingkungan dan asupan protein dengan infeksi kecacingan pada balita usia 24-59 bulan di Kabupaten Aceh Tengah - Vanessa Yudha Azizul Ilmi; Ahmad Syauqy; Etika Ratna Noer (Poltekkes Kemenkes Aceh, 2024)
Background: Soil transmitted helminth(STH) infection is an infection caused by a group of nematode worms that is transmitted through parasite larvae or eggs that develop in the soil and then come into direct contact with humans. Helminth infections have a relationship with hygiene practices and environmental sanitation, in addition to adequate nutritional intake that makes the body's immune system strong so that it can prevent and fight infections, one of these important nutrients is protein.Objectives: To analyze the relationship between hygiene, environmental sanitation and protein intake on helminthiasis infection among toddlers aged 24-59 monthsMethods: Analytical research using a cross-sectional study in Atu Lintang District, Central Aceh Regency conducted in August-September 2023. The subjects used in this study were toddlers aged 24-59 months as many as 100 toddlers whose sampling used purposive sampling method. Data were collected by observation and interviewing the hygiene questionnaire, environmental sanitation and Semi quantitative Food Frequency Questionnaire (SQ-FFQ) to determine the adequacy of protein intake. Stool sample examination using the Kato Katz method. Data were analyzed using the Fisher Exact test with a significance level of 95%.Results: The results showed that 9% of toddlers were infected with STH and 91% were not infected with STH. Hand washing (p=0,002) and nail hygiene (p=0,000) were significantly associated with STH infection while footwear use (p=1,000), environmental sanitation (p=0,086) and protein intake (0.078) showed no significant association.Conclusion: In this study, the hygiene practices of hand washing and nail hygiene had a significant association with helminthiasis infection.